Edukasi Prilaku Hidup Bersih Dan Sehat (PHBS) Bagi Siswa Sekolah Dasar Melalui UKS - Ryan Agus Faisal Hasibuan; Fitriyani Nasution; Selfira Dewi Arimbi (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Clean and Healthy Living Behavior (PHBS) is a strategic effort to improve public health from an early age. Elementary schools are ideal environments to instill PHBS values because children are at a developmental stage where habits are easily shaped. However, observations show that many students still have poor hygiene habits, such as not washing hands properly, consuming unsafe snacks, and neglecting school cleanliness.This PHBS education activity through the School Health Program (UKS) aims to improve students’ knowledge, attitudes, and healthy living practices. The implementation methods include interactive health education, handwashing demonstrations, environmental cleanliness simulations, and classroom cleanliness competitions. The evaluation results show a significant increase in students’ PHBS knowledge from 56% to 92%, accompanied by positive behavioral changes such as regular handwashing and proper waste disposal. This program demonstrates that an educational approach through UKS is effective in fostering clean and healthy living habits among elementary school students. It is expected that similar programs will continue sustainably with the involvement of teachers, health workers, and parents to create a healthy and supportive school environment for children’s growth and development.